Assesment of Health-Related Quality of Life with Patient Chronic Kidney Disease - Fajriansyah Fajriansyah; Mujriah; Zulfahmidah (Pengurus Pusat Ikatan Apoteker Indonesia, 2020)
Measuring the quality of life can be used as a reference for the success of an action or therapy as well as initial data in formulating the right action for the patient. This study aims to provide an overview of the quality of life of patients with chronic renal failure who seek treatment at the Hasanuddin University hospital. The research design used was an observational cross-sectional design with data collection carried out by filling out a questionnaire prospectively. The subjects of the study were chronic renal failure patients undergoing hemodialysis who met the inclusion criteria and were selected using a non-random sampling technique by means of total sampling. The patient's quality of life was measured using the Kidney Disease Quality of Life Short Form (KDQOL-SF™) Indonesian version 1.3 questionnaire. A total of 30 patients were willing to participate in this study. The results of the study on 30 patients with chronic renal failure, there were 7 out of 19 scale/item having a not good, namely burden of kidney disease, work status, sleep, physical functioning, role-physical, pain, and general health. The average value of 19 scale/item shows an average score of> 59.37, which is 63.86 which belongs to the good quality of life category.